Electrochemical Characterization of Cellulose Acetate/Chitosan Membrane in Presence and Absence of Nonionic Surfactant in Monovalent Electrolytic Solution - Nath, Satya; Tiwari, A.K.; Tiwari, P.K. (Asian Journal of Chemistry, 2021)
The influence of surfactant on cellulose acetate/chitosan membrane has been investigated. A basic approach to cellulose acetate/chitosan membrane is also mentioned. Nonionic surfactants are disrupted the normal permeability of the characteristic membrane. Electrochemical characterization such as conductance, flow, flux and permeability are measured in various concentrations of the electrolyte and surfactants. Membrane potential is determined by the combination of the properties of ions of the electrolyte, surfactant and membrane. The synthesized membrane was found to be cation selective with measured membrane potential found to be negative in all cases. The value of membrane potential was varying in different concentration of the electrolyte and surfactant. The Teorell Meyer and Sievers (TMS) theoretical method was employed for calculating the Transport number, perm selectivity and fixed charge density of the membrane by using the data of membrane potential across normal and surfactant modified membrane with electrolytic solution of NaCl. The variation of fixed density and perm selectivity also depends on the concentration of the electrolyte and surfactant (Tween 20 and Tween 60).